Pendayagunaan Irigasi Airtanah Menunjang Budidaya Tanaman Secara Produktif pada Lahan Kering - Muhammad Aqil; R.H. Anasiru; I.U. Firmansyah; Riyadi Riyadi; Sigit S. Arief (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
The utilization of shallow groundwater well to support cropping pattern in dry land area should be directed to increase land and water productivities through proper irrigation management and effective operation of groundwater irrigation pump. By the concept that a certain plant needs a certain amount of transpired water through it's leaves to produce 1 kg dry product during it's production cycle, an attempt is done to determine technical and economic aspects of the groundwater irrigation system to utilize water and energy efficiently by improving the conjunctive use of rainfall and groundwater irrigation in dry land area. A set of centrifugal pump (ɸ 2